2008
DOI: 10.3748/wjg.14.944
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of Solitary Peutz-Jeghers-type hamartomatous polyp in the duodenum

Abstract: A solitary Peutz-Jeghers-type hamartomatous polyp in the duodenum is rare, and few reports have described its characteristic endoscopic features. We describe three cases of solitary Peutz-Jeghers-type hamartomatous polyp and their endoscopic findings in detail. The polyp in all of our three cases showed an irregularly lobular or nodular surface, whereas adenomas often show a regularly nodular or granular surface. The color of the polyp was whitish in all of our cases. In the present cases, close observation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…These lesions have been described as having a lobular or nodular surface, whitish colour and whitish spots on the surface. Endoscopic removal is indicated as there is a small risk of malignant transformation [Suzuki et al 2008].…”
Section: Submucosal Lesionsmentioning
confidence: 99%
“…These lesions have been described as having a lobular or nodular surface, whitish colour and whitish spots on the surface. Endoscopic removal is indicated as there is a small risk of malignant transformation [Suzuki et al 2008].…”
Section: Submucosal Lesionsmentioning
confidence: 99%
“…A literature review showed only 13 similar reports in 23 patients of solitary duodenal hamartomas (Table 1). [2][3][4][11][12][13][14][15][16][17][18][19][20] Malignant transformation has only been reported twice. 4,20 The fi rst case was an 84-year-old woman who presented with gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…A search of case reports on the MEDLINE database up to 2014 using the terms "solitary", "duodenum", and "hamartomatous polyp", but without PJS, identified 19 patients in 13 studies published in English with solitary-PJ type polyps in the duodenum, including the patient described here [2,[5][6][7][8][9][10][11][12][13][14][15] (Table 1). Age at onset ranged from 23-89 years (mean ± SD: 60.3 ± 20.1 years).…”
Section: Discussionmentioning
confidence: 99%